1H NMR brain metabonomics of scrapie exposed sheep. Issue 7 (16th July 2015) - Scano, Paola; Rosa, Antonella; Incani, Alessandra; Maestrale, Caterina; Santucciu, Cinzia; Perra, Daniela; Vascellari, Sarah; Pani, Alessandra; Ligios, Ciriaco
<x xml:space="preserve">Abstract</x> While neurochemical metabolite modifications, determined by different techniques, have been diffusely reported in human and mice brains affected by transmissible spongiform encephalopathies (TSEs), this aspect has been little studied in the natural animal hosts with the same pathological conditions so far.